Perception and awareness of circular economy options within sectors related to agriculture in Argentina. (1st November 2022) - Rótolo, G.C.; Vassillo, C.; Rodriguez, A.A.; Magnano, L.; Milo Vaccaro, M.; Civit, B.M.; Covacevich, M.S.; Arena, A.P.; Ulgiati, S.
Abstract: The current socio-economic model based on a linear approach is being challenged by resource scarcity, negative environmental impacts and socio-economic constraints. Consequently, cycling approaches or circular economy (CE) paradigm is gaining attention. Business as usual is no longer possible and the model and criteria proposed by circular economy are a sustainable alternative that effectively couples natural with human-made systems. A model in which citizens in each of their social roles have a lot to say and do. However, implementation in Argentina is very slow and it is only applied at some level by companies or in urban residues recycling in a small number of cities. Additionally, social skepticism and lack of information about what circular economy embraces is still perceived. The objective of this exploratory paper is to identify the present level of awareness, the current situation and the expectations regarding the transition towards a circular economy approach within Argentina's agricultural sectors based on an opinion and perception survey. The aim of the study is to establish a baseline understanding and an interpretative framework to aid researchers and policymakers in promoting and increasingly implementing circular economy criteria in specific sectors. The study analyzes by a descriptive statistic a survey (n = 534) of selected actors related to the agricultural sector, i.e., farmers, agronomists (including agricultural engineers, veterinarians, and biologists), agrifood companies, and also directly related sectors, such as education and public administration. The anonymous questionnaire was divided into three parts: i) demographic characterization, ii) general awareness about transition towards circular economy (concept, current situation, features, advantages, drivers, obstacles and governance) within the region where the respondent operates, and iii) specific aspects within each selected sector. Results showed that the selected sectors perceived a common vision about the concept of CE "as a more sustainable production and consumption model", and with some differences, they have mainly sensed that the transformation process is still both not initiated and at its initial steps. Respondents selected to focus on recycling/reusing as well as on the integration between productive units. Political, economic and environmental awareness as well as technological skills have been chosen as barriers. Consequently, they chose to invest on education and research, noticing the citizens/society as the main agent of transformation. Since the challenge is to find organized and progressive steps to build interactions, programs, actions and legislation to favor the integral (between sectors) and internal (within a sector) transition, indicators for monitoring as well as policies, priorities and perspectives have been highlighted to contribute to boost the transformation towards a circularity approach.